Effects of exercise training on depression and anxiety with changing neurotransmitters in methamphetamine long term abusers: A narrative review - Arazi Hamid; Dadvand Seyedeh Shiva; Suzuki Katsuhiko (Biomedical Human Kinetics, 2022)
Study aim: It is generally accepted that methamphetamine (MA) is a highly addictive psychostimulant which copies functions of certain neurotransmitters in the brain, and emits dopamine and serotonin in the brain. Frequent abuse of methamphetamine damages dopaminergic and serotonergic nerve endings at different sites of brain and also increases the anxiety and depression. Exercise seems to reverse physiological and neurological damages due to previous MA dependents and help to reduce anxiety and depression in this population. The aim is to determine the effect of exercise training on neurotransmitters and rate of depression and anxiety in chronic methamphetamine abusers based on a literature review.